Utilization of Online Media in the 2020 Simultaneous Regional Head Election Campaign in Semarang - Beti Wulansari; Haris Isa Pamungkas (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
This article highlights how the use of online media as a campaign tool amid the Corona Virus Disease 19 pandemic in the Simultaneous Election of Mayor and Deputy Mayor of Semarang in 2020. focused The problem on how the challenges faced by General Election organizers and Candidate Pairs in organizing campaigns through online media. To approach this problem, used Rogers and Storey's campaign theory references. The campaign is one of the crucial stages of the election. Still, during the pandemic, the mass mobilization typical of the movement is limited and prioritized online media. Data were collected through observation, survey questionnaires, and document literacy and analyzed qualitatively. This study concludes that the team successfully played a campaign strategy through the internet during this pandemic, especially online and social media. Online media in this campaign also assisted General Election Supervisory Agency Election organizers as a supervisory function in the Implementation of the campaign. However, in campaigning efforts through online media, it is necessary to encourage various parties to create good political education in the community.